Detecting tropical cyclones in regional climate model simulations over the Cordex-South East Asia domain - TIBAY, JENNIFER (Archīum Ateneo, 2018)
The study analyzed the capability of the downscaled simulations of the Southeast Asia Climate Downscaling / Coordinated Regional Climate Downscaling Experiment Southeast Asia (SEACLID/CORDEX-SEA) in representing tropical cyclone (TC) climatology, in terms of pattern, intensity, frequency, and lifetime, in both historical and near future projection with RCP 4.5 and RCP 8.5. A modified vortex tracking algorithm based on the methodology of Phan et al. (2015) is used as the detection method to detect TCs in the simulations of SEACLID/CORDEX-SEA from the period of 1986 to 2005. The detection method examines a wide range of criteria in detecting TCs: vorticity, outer core wind strength, sea level pressure anomaly and temperature anomaly from four pressure levels (300-, 500-, 700-, and 850 hPa). Results are validated using the best tracks of the Joint Typhoon Warning Center (JTWC) from 1986 to 2005. Based from the historical results, the model simulations underestimated the total number of TCs and the average TC days for the said period but it captured the annual variation of the total number of TCs. In the near future projection there is a decrease in the total number of TC per year but there is no significant change in the intensity and lifetime of the near future projections. This study is a good first step in efforts to help understand and consequently mitigate TC-related disasters for regions in SEA.